1969
DOI: 10.2118/2155-pa
|View full text |Cite
|
Sign up to set email alerts
|

Well Test Interpretation of Vertically Fractured Gas Wells

Abstract: In the analysis of field data it is important to bear in mind the proper relationship between the radial flow period and the linear proper relationship between the radial flow period and the linear flow period. The transition between these periods is quite long and can be misinterpreted as being the linear flow period. Another factor that can complicate analysis is turbulence. Introduction The trend in gas well testing has been to rely more on be early-time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…Most of the relevant papers have been devoted to short-and intermediate-time well testing: pressure build up, well storage effects, and flow tests. The classical papers by Prats (1961), Russell and Truitt (1964), Wattenbarger and Ramey (1969), Gringarten and Henry (1974) should be mentioned in this context. A 1-D (rectilinear) transient flow analysis was also applied to long-time production from hydrofractured wells in ultra-low-permeability formations.…”
Section: Brief History Of Predictions Of Well Productionmentioning
confidence: 99%
“…Most of the relevant papers have been devoted to short-and intermediate-time well testing: pressure build up, well storage effects, and flow tests. The classical papers by Prats (1961), Russell and Truitt (1964), Wattenbarger and Ramey (1969), Gringarten and Henry (1974) should be mentioned in this context. A 1-D (rectilinear) transient flow analysis was also applied to long-time production from hydrofractured wells in ultra-low-permeability formations.…”
Section: Brief History Of Predictions Of Well Productionmentioning
confidence: 99%
“…Many authors (Wattenbarger and Ramey, 1969;Holditch and Morse, 1976;Guppy et al, 1982aGuppy et al, ,b, 1988Settari et al, 2000;Nunez et al, 2003;Hagoort, 2004) have stated that nonDarcy effects manifest itself as a positive skin factor, which is linearly proportional to the production rate; hence, it can be treated as ratedependent skin similar to non-fractured wells. Consequently, Eq.…”
Section: High-flow Rate Production Effectsmentioning
confidence: 99%
“…One of first papers published on high-production rate effect on the behavior of fractured systems was by Wattenbarger and Ramey (1969). They concluded that non-Darcy effects caused by high-flow rate have more adverse impact on the gas flow behavior in the fracture than in the surrounding formation.…”
Section: Introductionmentioning
confidence: 99%
“…Holditch and Morse (1976) performed work involving non-Darcy flow in hydraulically fractured wells. Their work was a follow up on speculation by Wattenbarger and Ramey Jr. (1969) that turbulence within the fracture itself is sometimes more important then turbulence within the formation. Holditch and Morse's work was accomplished via numerical simulation and showed that for gas wells, nonDarcy flow within the fracture can have a significant effect on well productivity and pressure transient response.…”
Section: Literature Reviewmentioning
confidence: 99%